2014
DOI: 10.1089/jwh.2014.4978
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Uterine Fibroid Research Through Utilization of Biorepositories Linked to Electronic Medical Record Data

Abstract: Background: Uterine leiomyomata (fibroids) affect up to 77% of women by menopause and account for $9.4 billion in yearly healthcare costs. Most studies rely on self-reported diagnosis, which may result in misclassification of controls since as many as 50% of cases are asymptomatic and thus undiagnosed. Our objective was to evaluate the performance and accuracy of a fibroid phenotyping algorithm constructed from electronic medical record (EMR) data, limiting to subjects with pelvic imaging. Methods: Our study p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 16 publications
2
21
0
Order By: Relevance
“…A validated phenotyping algorithm with a positive predictive value of 96% was used to identify fibroid cases (30). We included AA women who were at least 18 years old, who had at least one documented fibroid and one pelvic imaging or surgery to treat fibroids, as indicated by the international classification of diseases, ninth revision, (ICD-9) or current procedural terminology (CPT) codes.…”
Section: Methodsmentioning
confidence: 99%
“…A validated phenotyping algorithm with a positive predictive value of 96% was used to identify fibroid cases (30). We included AA women who were at least 18 years old, who had at least one documented fibroid and one pelvic imaging or surgery to treat fibroids, as indicated by the international classification of diseases, ninth revision, (ICD-9) or current procedural terminology (CPT) codes.…”
Section: Methodsmentioning
confidence: 99%
“…The study by Feingold-Link et al 5 published in the December issue offers a new approach to solving this problem. They present an algorithm to identify cases with fibroids and controls without fibroids using diagnostic codes, clinical notes, and imaging findings.…”
mentioning
confidence: 99%
“…5 In genetic studies of fibroid development, it may be necessary to have complete case ascertainment, which would occur at menopause, when development of fibroids ceases. FeingoldLink et al demonstrated high reliability of the algorithm in women over age 55.…”
mentioning
confidence: 99%
See 2 more Smart Citations